The Development of Geotourism with the Use of 3D Digital Cave Model. A Case Study of the Bear Cave, Slovakia - Tometzová, Dana; Hlavňová, Barbara; Drevko, Slavomír; Pukanská, Katarína; Bartoš, Karol; Bieda, Agnieszka; Kseňak, Ľubomír (Geomatics and Environmental Engineering, 2020)
Cave tourism (speleotourism) is very popular all over the world within the broader category of geotourism. Slovakia is also well‑known for its karst areas and caves, but most of them are not freely open to the public. This paper presents how to make a cave "œaccessible" without physically entering it. This can be facilitated through the use of digital 3D models. Visitors are then able to experience cave tours through 3D projections and 3D cinema. This would allow people with disabilities and those with claustrophobia to enjoy caving. An added advantage is that the cave environment remains untouched. This paper provides a comprehensive scan of the Bear Cave using Leica ScanStation C10 terrestrial laser scanner. During the 3D modelling of the Bear Cave, Trimble RealWorks software was used to process and analyze the large data sets recorded by the scanner. As a result, not only were visualizations and images of 3D models from the cave obtained, but also a 3D animation was made using the Bentley Pointools software. The information included in this paper has been compiled from all phases of the measuring and data processing of the Bear Cave.